Textural, rheological, and structural properties of turkey and chicken gelatins from mechanical deboning residues - Kurt, Abdullah; Toker, Omer Said; Akbulut, Mehmet; Coklar, Hacer; Ozmen, Duygu; Ozcan, Yilmaz; Argun, Mustafa Samil (Wiley, 2024)
Large amounts of collagen-rich by-products are generated in poultry processing. In particular, gelatin from the by-products of turkey processing is limited. Gelatin extraction from turkey and chicken MDRs (mechanically deboning residue) was the purpose of this study. Both materials were modified at the highest swelling pH for chemical denaturation of collagen and hot water extraction of gelatin was performed at the optimum temperature-time, which was determined to be pH 1.0 and 80 degrees C-6 h, respectively. In these conditions, yields of 9.90% turkey gelatin (TG) and 13.85% chicken gelatin (CG) were produced. They demonstrated similar viscosity, gel strength, and lightness values of 72-73 g, 2.5-2.7 mPas, and 31, respectively. These results are close to those of bovine gelatin (BG). TG with 239.78 g Bloom exhibited higher strength than CG (225.27 g) and BG (220.00 g). The melting and gelation temperatures of CG and BG were 21 and 30 degrees C, respectively, while those of TG were 19 and 28 degrees C. Imino acids (proline + hydroxyproline) of TG (22.82%) were higher than those of CG (20.73%). Fourier transform infrared spectroscopy (FTIR) analysis revealed secondary structure and functional groups of CG and TG similar to those of BG. CG displayed a higher thermal transition temperature than BG, while TG exhibited the highest temperature sensitivity, according to the differential scanning calorimetry (DSC) analysis. In conclusion, TG showed higher potential for effective utilization with higher bloom and imino acids. Overall, turkey and chicken MDRs are a promising and potential alternative source to produce gelatin with comparable properties to bovine gelatin for intended food applications as well as for pharmaceutical and cosmetic fields. This is a novel research paper on the production of gelatin from alternative sources, turkey and chicken MDRs (mechanically deboning residues), as by-products of poultry processing. The findings of this study will be useful to the literature and the food science and technology.image
Keywords: gelatin extraction; gelling; mechanically deboning residues; rheology; texture